Geology and structure of the Serre Massif upper crust: a look in to the late-Variscan strike–slip kinematics of the Southern European Variscan chain. Issue 2 (1st December 2022) - Ortolano, G.; Pagano, M.; Visalli, R.; Angì, G.; D'Agostino, A.; Muto, F.; Tripodi, V.; Critelli, S.; Cirrincione, R.
ABSTRACT: A new geological-structural map of the southern Serre Massif (SM), in the south-central part of the Calabrian-Peloritani-Orogen (CPO), is provided. CPO is a ribbon-like microplates puzzle, originally belonging to the southern European Variscan Belt and, later involved into the Alpine geodynamics of the central Mediterranean Area. The SM represents one of the key European Variscan basement relicts, because of its exhumation mechanisms as well as for the absence of any Alpine metamorphic overprint. This map has the aim to better delineate the sequence of the Variscan blasto-deformational relationships consisting in a prograde multistage history, followed by an extensional/transpressional multistage retrograde evolution, which triggered the intrusion of the former plutonic products. The mylonitic fabric resulted finally replaced by the effects of the late- to post-kinematic plutonic intrusions coeval with a former late-Variscan exhumation stage, followed, during Mesozoic, by carbonate platform sedimentation, before to be completed exhumed during the Oligocene-Miocene Alpine stages.